Legal Certainty in Residential Lease Agreements: a Comparative Study between Indonesia and Australia - Muhammad Rifqi Rafi Drajat; Nun Harrieti; Sheila Eldi Azzahra (Universitas Islam Negeri Walisongo Semarang, 2025)
Differences in legal systems between Australia and Indonesia have the potential to impact the fulfillment of the legal requirements of an agreement, including in the context of rental contracts. Australia is a leading destination for higher education for Indonesian students, and in 2021, the number of Indonesian students in Australia was recorded as the highest among study destination countries. This situation makes a comparative study of the contract law of the two countries relevant, particularly to understand potential differences in the formation, implementation, and resolution of contractual disputes. This analysis is essential so that parties, especially Indonesian students in Australia, can anticipate the legal consequences of their legal actions in rental practices. The research method used in this study is normative juridical with analytical descriptive research specifications. The results show that the differences in the legal requirements of agreements between Indonesia and Australia are based, in part, on the existence of the Tellinty Form, which emphasizes the need for written contracts. The practice of renting residential properties in Australia uses a special form, as regulated by the Tendential Renancies Act, for its completeness and content. If the landlord does not execute a written contract, there will be special consequences. Meanwhile, in Indonesia, contract-making practices are still based on verbal agreements. Likewise, even when written, many do not comply with the standard rental contract format stipulated in Government Regulations. This research contributes to the analysis of student housing rental agreements as a basis for reforming rental law in Indonesia. Perbedaan sistem hukum antara Australia dan Indonesia berpotensi mempengaruhi pemenuhan syarat sah suatu perjanjian, termasuk dalam konteks kontrak sewa-menyewa. Australia merupakan salah satu tujuan utama pendidikan tinggi bagi mahasiswa Indonesia, dan pada tahun 2021 jumlah mahasiswa Indonesia di Australia tercatat sebagai yang tertinggi di antara negara tujuan studi. Kondisi ini menjadikan kajian komparatif mengenai hukum kontrak kedua negara relevan, terutama untuk memahami potensi perbedaan dalam pembentukan, pelaksanaan, dan penyelesaian sengketa kontraktual. Analisis ini penting agar para pihak khususnya mahasiswa Indonesia di Australia dapat mengantisipasi akibat hukum dari tindakan hukum yang mereka lakukan dalam praktik sewa-menyewa. Metode penelitian yang digunakan dalam penelitian ini adalah yuridis normatif dengan spesifikasi penelitian deskriptif analitis. Hasil menunjukan bahwa perbedaan syarat sah perjanjian antara negara Indonesia dengan Australia salah satunya didasari oleh adanya Ceritainty Form yang menekankan perlunya hukum kontrak yang harus dilakukan secara tertulis. Praktik sewa menyewa tempat tinggal di Australia menggunakan form khusus sebagaimana yang telah diatur kelengkapan dan isiannya antara penyewa dan pemilik tempat tinggal sebagaimana dalam Tendencial Renancies Act. Apabila pemilik tempat tinggal tidak melaksanakan kontrak secara tertulis, maka akan ada konsekuensi-konsekuensi khusus yang akan didapat. Sedangkan di Indonesia, praktik pembuatan kontrak masih didasarkan pada perjanjian secara lisan. Begitupun jika dilakukan secara tertulis, masih banyak yang tidak sesuai dengan standar format pengisian kontrak sewa sebagaimana yang telah diatur dalam Peraturan Pemerintah. Penelitian ini berkontribusi dengan menganalisis perjanjian sewa tempat tinggal mahasiswa sebagai landasan untuk mereformasi hukum sewa menyewa di Indonesia. Keywords: Agreement; Contract; Legal Certainty; Residential Tenancy.